Conceptual Model Of Supply Chain Center For Msmes In Indonesia - et. al., Setijadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
MSMEs in Indonesia are one of the main drivers of the economy. There are many MSMEs with creative ideas and goods offered to the public but there are yet many weaknesses faced by MSMEs. The weaknesses of MSMEs in Indonesia, among others, are the lack of access to market information. MSMEs are often also constrained by a lack of funds for working capital and investment. The skills of human resources are still low, the technology used shows the same level. Logistics and supply chain issues also alleviate the competitiveness of local products by MSMEs in Indonesia. MSMEs have not been integrated into the supply chain. Obstacles for MSMEs also relate to economic scale. The small scale of production results in a small volume of raw material procurement and product delivery, which induces higher costs and lessens competitiveness. With these conditions, the actors in an MSMEs center need to collaborate. Hence, it is necessary to establish a Supply Chain Center (SCC) in MSME centers or industrial areas by the government and the private sector. Promoting economic scale is carried out in the procurement of raw materials, inventory storage, and delivery of finished products. SCC can also manage shared facilities such as warehousing and transportation fleets. SCC does not only handle goods, but also information, services, and fund which will increase the productivity and competitiveness of MSMEs. The development of the SCC must involve stakeholders, namely the central government, local governments, associations